Computer Use Problems and Accommodation Strategies at Work and Home for People With Systemic Sclerosis: A Needs Assessment. - Baker, Nancy A.; Aufman, Elyse L.; Poole, Janet L. (American Journal of Occupational Therapy)
OBJECTIVE. We identified the extent of the need for interventions and assistive technology to prevent computer use problems in people with systemic sclerosis (SSc) and the accommodation strategies they use to alleviate such problems. METHOD. Respondents were recruited through the Scleroderma Foundation. Twenty-seven people with SSc who used a computer and reported difficulty in working completed the Computer Problems Survey. RESULTS. All but 1 of the respondents reported one problem with at least one equipment type. The highest number of respondents reported problems with keyboards (88%) and chairs (85%). More than half reported discomfort in the past month associated with the chair, keyboard, and mouse. Respondents used a variety of accommodation strategies. CONCLUSION. Many respondents experienced problems and discomfort related to computer use. The characteristic symptoms of SSc may contribute to these problems. Occupational therapy interventions for computer use problems in clients with SSc need to be tested.